2022
DOI: 10.1073/pnas.2022050119
|View full text |Cite
|
Sign up to set email alerts
|

Bivalent recognition of fatty acyl-CoA by a human integral membrane palmitoyltransferase

Abstract: S-acylation, also known as palmitoylation, is the most abundant form of protein lipidation in humans. This reversible posttranslational modification, which targets thousands of proteins, is catalyzed by 23 members of the DHHC family of integral membrane enzymes. DHHC enzymes use fatty acyl-CoA as the ubiquitous fatty acyl donor and become autoacylated at a catalytic cysteine; this intermediate subsequently transfers the fatty acyl group to a cysteine in the target protein. Protein S-acylation intersects with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Therefore, we reasoned that removal of the methyl amide from DPP-5 would both minimize steric clashes and result in a better acyl-CoA mimic ( PTP-1 ) (see Figure A). Docking against zDHHC20 revealed a tightly bound ligand–receptor complex, but also that the probe did not engage a highly conserved key residue of the basic patch, Lys135 , (Figure S2 in the Supporting Information). In silico screening to maximize this ADP-binding pocket interaction demonstrated that replacement of succinic acid with glutaric acid ( PTP-2 ) resulted in further optimized interactions (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we reasoned that removal of the methyl amide from DPP-5 would both minimize steric clashes and result in a better acyl-CoA mimic ( PTP-1 ) (see Figure A). Docking against zDHHC20 revealed a tightly bound ligand–receptor complex, but also that the probe did not engage a highly conserved key residue of the basic patch, Lys135 , (Figure S2 in the Supporting Information). In silico screening to maximize this ADP-binding pocket interaction demonstrated that replacement of succinic acid with glutaric acid ( PTP-2 ) resulted in further optimized interactions (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, whether DHHC3 is the specific palmitoyltransferase for LAMTOR1 deserves further investigations. Recently, Lee et al indicated that the addition of palmitoyl-CoA to an inactive mutant of DHHC20 (hDHHS20) can be successfully crystallized [ 24 ]. This crystal structure revealed that palmitoyl-CoA locates at the interface between two hDHHS20 monomers and partially inserts into the acyl chain binding cavity, which gives the clue to improve crystallization conditions to obtain the DHHC3 structure at atomic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of a complex formed by hDHHC20 with its inhibitor 2-bromopalmitate (2-BP) to mimic the acyl intermediate was further solved, showing that the acyl chain is inserted into an enzyme cavity composed of the four TM helices within the membrane bilayer, in which TM3 contributes the most in contact with the acyl chain [ 23 ]. They further reported a structure of a catalytically inactive mutant hDHHS20 in a complex with palmitoyl-CoA and elucidated that the polar and ionic interactions between the CoA headgroup and the cytosolic domain are also important for the substrate binding [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…We aimed to mimic the native substrate of zDHHC20, acyl CoA, which interacts not only with the lipid-binding pocket but also with CoA-binding components, including an ADP-binding pocket. In fact, it has been shown that bivalent recognition is critical for DHHC–substrate binding . The CoA can be seen as three elements: a cysteamine, a pantothenic acid linker, and a 3′-phosphoadenosine diphosphate.…”
mentioning
confidence: 99%
“…In designing the next generation of DHHC inhibitors, improving selectivity will likely mean reducing the lipophilicity and/or targeting additional binding motifs, such as the CoA binding pocket. In the present study, we report an expanded structure–activity relationship (SAR) study of CMA and its derivatives against zDHHC20 (Figure ), the most structurally characterized family member, and the homologous zDHHC2, with an eye toward understanding the limits and potential of the acrylamide scaffold.…”
mentioning
confidence: 99%